Sejarah Perkembangan Kurikulum di Indonesia Serta Kurikulum Bahasa Indonesia - Handriani Aprillia Hutajulu; Lestari Purba; Rosmawaty Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the historical development of the curriculum in Indonesia as well as the dynamics of the Indonesian Language curriculum as an important part of the national education system. The method used is a literature study by analyzing various literary sources related to curriculum changes over time. The results of the study indicate that the curriculum in Indonesia has undergone significant changes, starting from the 1947 Curriculum to the Merdeka Curriculum, influenced by social, political, cultural factors, as well as the development of science and technology. The Indonesian Language curriculum has also undergone a transformation, from a grammar-based approach to a communicative and text-based approach that emphasizes critical thinking skills, literacy, and contextual language proficiency. These changes reflect the government's efforts to improve the quality of education and adapt learning to the needs of the times. Thus, understanding the historical development of the curriculum and the Indonesian Language curriculum is important as a foundation for developing relevant and adaptive learning in the modern era.